Seasonal anisotropy in handedness. - Jones, G; Martin, M (2008)
The preference for using either the left or the right hand has been linked to important human characteristics such as language lateralisation within the cerebral hemispheres, and evidence has been reported that the proportions of different types of handedness may be influenced by factors such as levels of maternal hormones and anxiety. Under such influences, it is possible in principle that distributions of handedness provide evidence of seasonal anisotropy, that is, variation in the direction of handedness for births in different parts of the year. The results of a number of studies are compared here, and shown to provide evidence of a significant tendency for the incidence of left-handed people to be higher among those born in the spring and ensuing months (March-July in the northern hemisphere) than among those born in the remainder of the year, at least among the male population.